Study on the Effect of Processing Parameters on the Extraction of Stevioside Using Ultrasonic Extractor - Nurul Husna, Hashim (2012)
Stevia rebaudiana is a sweet, green leaves that contain high amount of sweetener but has no calories. Inside stevia rebaudiana leaves, there are many sweet components includes stevioside, rebaudioside A, B, D, E and dulcoside. Among these sweet components, stevioside is the most abundant component. Stevioside is a natural sweetener and 300 times sweeter than sucrose. It is an alternative to sugar, that suitable for people who suffer from diabetes and hypertension because it has a negligible effect on blood glucose. In this present study, stevioside was extracted using an ultrasonic extraction method. They were 3 parameters that have been studied. The screening of the best extraction solvents (distilled water, ethanol 95% and 70% ethanol aqueous) were firstly investigated before designing the experiment by using one-factor-at-one time method. The 3 parameters involved included the ratio of leaves/solvent, extraction time and the ultrasonic frequency. Based on the result obtained, distilled water is the best extraction solvent with the ratio of leaves to solvent at 4:30 (w/v), extraction time of 20 minutes and the sonicator frequency at 20 kHz. It can be concluded that by using suitable types of solvent ratio, extraction time and sonicator frequency, the highest yield of stevioside have been obtained.